'Single-checked' Patient Group Directions during initial nurse assessment within paediatric emergency departments of the UK and Ireland. (June 2018) - Bird, Chris K.; Sinclair, Anthony G.; Hartshorn, Stuart
Abstract : Objective: Double checking medications at initial assessment within paediatric emergency departments (EDs) has the potential to delay patient flow, and doubt has been cast on the efficacy of double checking in all but high-risk medications. We aimed to benchmark current practice for the use of Patient Group Direction (PGD) medications at initial assessment in EDs within the Paediatric Emergency Research UK and Ireland (PERUKI) network, with a focus on the use of 'single-checker' PGDs. Methods: Online survey was distributed to the research representative at each PERUKI site. The survey was open for 5 weeks (from March 2015 to April 2015) and was completed by any appropriate clinician within the site. Results: The response rate was 84% (36/43 EDs). From these, 22 out of 36 (61%) EDs were using single-checker PGDs. The commonest single-checked medications in use were paracetamol and ibuprofen for pain. Among PERUKI sites, 21.9% of EDs reported drug errors related to standard (double-checked) PGDs, whereas 13.6% of those with single-checked PGDs reported drug errors (Fisher's exact test with significance level of 0.05, P =0.501). The commonest errors reported were duplicated dose, incorrect weight, incorrect volume drawn up, contraindication missed. Conclusion: Single-checker PGDs are currently in use in nearly two-thirds of PERUKI sites. No evidence of increased medication errors was reported with this practice; however, more detailed studies are required to support this finding and to inform best practice. Abstract : Supplemental Digital Content is available in the text.